Ergonomics in Asia development, opportunities, and challenges ; selected papers of the 2nd East Asian Ergonomics Federation Symposium (EAEFS 2011), Hsinchu, Taiwan, 4-8 October 2011 - Shih, Yui-Chuah; Liang, Sheau-Farn Max (CRC Press, 2012)
For the past decade, the rapid development of the ergonomics disciplines as well as the fast growing economy in the Asian region have been attracting the attention of the international ergonomics community. Although East Asia has been changing from a traditional agriculture-oriented society into a modern industry-oriented society and its economy covers a great deal of shared interests across the continents, yet the ergonomics related knowledge and practice are still in its infancy. Because of the geographic proximity and a strong historical, cultural and technology affinity, it is vitally important to maintain good communication and cooperation among the individuals as well as among the ergonomics organizations in the region. This symposium, EAEFS, has provided supporting ergonomics organizations and interested participants a forum to exchange ideas, build friendship, foster greater understanding of and among these individuals and organizations, and develop perspectives concerning ergonomics issues in this region and beyond. This volume contains the selected papers presented at the Second East Asian Ergonomics Federation Symposium (EAEFS), held from October 4 - 8, 2011 at the National Tsing Hua University in Taiwan. The Second EAEFS, endorsed by the International Ergonomics Association (IEA), aims to consolidate the established ties within East Asia and to extend the cooperation among ergonomics researchers, professionals, and practitioners in the region to other regions in Asia and the world. Senior scholars and leaders from Asian countries have shared their wisdom, experience, insights, and visions on past, current and future ergonomics efforts in Asia. The papers contributing to this book address the latest research and application in accordance with the theme of the symposium, "Ergonomics in Asia: Development, Opportunities and Challenges," and cover the following areas: Virtual Environments & Design, Aging & Work Ability, Usability & Interface, Biomechanics & Anthropometry, and Occupational Safety & Health.